Parameterization of the mid-trimester drop in blood pressure trajectory during pregnancy and its utility for predicting preeclampsia. Issue 7 (July 2020) - Mi, Baibing; Wen, Xiaozhong; Li, Shanshan; Liu, Danmeng; Lei, Fangliang; Liu, Xin; Wang, Duolao; Li, Xuelan; Shittu, Abdal Aziz T.; Dang, Shaonong; Yan, Hong
Abstract : Objectives: The purpose of this study was to parameterize mid-trimester drop in blood pressure (BP) trajectory during pregnancy and to evaluate its utility for predicting preeclampsia. Methods: To develop parametric models for BP trajectory during pregnancy, we used data from 7923 Chinese pregnant women with 24 810 routine antenatal care visits. Then, we evaluated the utility of BP trajectory parameters for predicting clinician-diagnosed preeclampsia in a separate sample of 3524 pregnant women from a randomized controlled trial of prenatal vitamin supplementation conducted in the same area. We focused on parameters related to the mid-trimester BP drop, including the gestational age and BP value at the nadir (lowest point), change in BP, velocity, and area under curve during two periods (from 12 weeks of gestation to the nadir and from the nadir to 33 weeks of gestation). Results: All participants in our analysis had a mid-pregnancy drop in their SBP, DBP, and mean arterial pressure (MAP) trajectories. There were high correlations (| r | > 0.90) among trajectory parameters of the same BP measure. The final prediction model included selective parameters of SBP, DBP, and MAP trajectories, prepregnancy BMI and gestational age at the first antenatal care visit. The area under the receiver-operating curve for predicting preeclampsia was 0.886 (95% confidence interval 0.846–0.926) in the training dataset and 0.802 (0.708–0.895) in the validation dataset. Conclusion: Our novel BP trajectory parameters are informative and can predict preeclampsia at a clinically acceptable level. Abstract : Supplemental Digital Content is available in the text